Identifying and Validating a Quantitative Trait Locus on Chromosome 14 Underlying Stearic Acid in a Soybean Landrace. Issue 2 (3rd March 2016) - Yan, Long; Deng, Yingying; Song, Qijian; Cregan, Perry B.; Chen, Pengyin; Lei, Yakun; Yang, Chunyan; Chen, Qiang; Di, Rui; Liu, Bingqiang; Zhang, Mengchen
ABSTRACT: Stearic acid (ST) is one of the saturated fatty acids (FAs) in soybean [ Glycine max (L.) Merr.] oil; lowering ST content may be helpful to reduce the potential health risks. In this study, recombinant inbred lines (RILs) derived from "Jidou 12" × "Heidou" cross were used to identify the QTL underlying ST content. As a result, two quantitative trait loci (QTL), designated as qSTE_6_1 and qSTE _ 14_1, were identified. The QTL qSTE_14_1 was also validated using residual heterozygous lines (RHLs) derived from the RILs. Analysis of the RHLs showed that two simple sequence repeats (SSR) markers, BARCSOYSSR_14_1033 and BARCSOYSSR_14_1079, located on chromosome 14, were tightly linked with qSTE_14_1 and could explain 50.2% and 43.1% of ST content variance at two locations. The allele from "Heidou" decreased the ST content from 3.28% to 2.92% at one location and from 3.55% to 3.01% at the other location. No significant effect of qSTE_14_1 on other FA contents was detected at either location. This study will assist in creating cultivars with lower ST.